2020
DOI: 10.1186/s12984-020-00742-x
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury neuroelectrochemical monitoring: behind-the-ear micro-instrument and cloud application

Abstract: Background: Traumatic Brain Injury (TBI) is a leading cause of fatality and disability worldwide, partly due to the occurrence of secondary injury and late interventions. Correct diagnosis and timely monitoring ensure effective medical intervention aimed at improving clinical outcome. However, due to the limitations in size and cost of current ambulatory bioinstruments, they cannot be used to monitor patients who may still be at risk of secondary injury outside the ICU. Methods: We propose a complete system co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…Figure 3 highlights the diversity of the biosensor technologies and their respective setups in tandem with microdialysis. For instance, Figure 3 A–D all have measured cerebral metabolites in dialysates of TBI patients, while Figure 3 E has quantified blood in the dialysates of subcutaneous interstitial fluid [ 45 , 47 , 49 , 50 , 65 ]. The development of biosensors in monitoring cerebral metabolism is challenging, and this is evident as no biosensor has been approved for clinical use.…”
Section: Review Of Sensor Technologies For Brain Metabolismmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 3 highlights the diversity of the biosensor technologies and their respective setups in tandem with microdialysis. For instance, Figure 3 A–D all have measured cerebral metabolites in dialysates of TBI patients, while Figure 3 E has quantified blood in the dialysates of subcutaneous interstitial fluid [ 45 , 47 , 49 , 50 , 65 ]. The development of biosensors in monitoring cerebral metabolism is challenging, and this is evident as no biosensor has been approved for clinical use.…”
Section: Review Of Sensor Technologies For Brain Metabolismmentioning
confidence: 99%
“…A few studies have shown both glucose and lactate measurements in TBI using electrochemical sensors integrated with microdialysis. Tageldeen and colleagues have achieved both glucose and lactate measurements using wearable electrochemical sensors [ 47 ]. They were able to demonstrate dynamic metabolic changes ranging from 0 to 1 mM with 0.25 mM steps.…”
Section: Review Of Sensor Technologies For Brain Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Wireless data logging systems that meet the standard for hospital use are becoming smaller and cheaper. A recent battery-powered potentiostat and wireless data transmission system with integrated biosensors and a microfluidic system for use with microdialysis manufactured by the Boutelle group costs less than £500 to build [260]. The Tiny FSCV potentiostat and wireless transmission system costs less than $75 [261] and is made with commercially available parts.…”
Section: Future Directionsmentioning
confidence: 99%